Rotated ℤ n -Lattices via Real Subfields of ℚ ( ζ 2 r ) - ANDRADE,A. A. (2019)
ABSTRACT A method for constructing rotated ℤ n-lattices, with n a power of 2, based on totally real subfields of the cyclotomic field ℚ ( ζ 2 r ), where r ≥ 4is an integer, is presented. Lattices exhibiting full diversity in some dimensions n not previously addressed are obtained.